O Programa Bolsa Família: identidade, subjetividade e integração social em Maracanaú-CE - Rocha, Sandoval Alves (Universidade do Vale do Rio dos Sinos, 2012)
The present article refers to a Case Study which treats about the influences of the Family Bourse Program, in the subjectivities of the beneficiaries in the Municip of Maracanaú-CE. Its objective is to stress the rebates of the program in the configuration of ideals and identifications of the beneficiaries, analyzing how these subjective articulations of ideals and their actions and interactions with society in which they live reflect. In order to obtain this aim, the investigation needed to utilize the qualitative method, recurring to bibliographical and documental research, besides demanding the application of semistructured interviews and participating observation as techniques for obtaining the data (data collection). In order to process the material collected, discourse analysis proved the most adequate proceeding to access the representational world of the persons interviewed. Among the results, the study stressed the emergence of positive feelings and the projection of better perspectives for the future, as well as it enabled the elaboration of action projects in daily life, viewing to face the situations of poverty, and searching to obtain better life conditions. Besides these subjective expressions, the research also visualized elaborations that lead to the questioning of the real possibilities of superation of poverty, since the situations of want and social vulnerability, as well as the experience of deficient public services (Education, Health, Social Assistance, among others) imply more structural measures, that surpass the sphere of a program of minimum income
Keywords: Pobreza; Programa de transferência de renda; Subjetividade; Idealizações; Integração social; Poverty; Program of rent transfer; Subjectivity; Idealizations; Social integration; ACCNPQ::Ciências Humanas::Sociologia